SWOT ANALYSIS OF SABRI KUPI COFFEE SHOP IN LHOKSEUMAWE CITY - Eka Saputri; Reza Mauliza; Assyifa Anzar Miati; Nurmila Tina; Intan Cahyani Rachman; Zulfikar Zulfikar; Yusmika Indah (HEI EMA : Jurnal Riset Hukum, Ekonomi Islam, Ekonomi, Manajemen dan Akuntansi, 2025)
This study aims to comprehensively analyze the Strengths, Weaknesses, Opportunities, and Threats (SWOT) of Sabri Kupi Coffee Shop, a local business located in Lhokseumawe City, Aceh. Sabri Kupi was established in 2020, coinciding with the COVID-19 pandemic, and has since positioned itself as one of the coffee shops serving traditional Acehnese coffee while providing a comfortable space for social interaction. The research employs a descriptive qualitative method, with data collected through direct observation of the coffee shop’s operations and semi-structured interviews with the owner, employees, and regular customers. The findings reveal that Sabri Kupi has several notable strengths, including its strategic location, the distinctive taste of Aceh coffee, a friendly atmosphere, and adequate facilities. However, the study also identifies weaknesses, particularly limited promotional strategies and heavy reliance on coffee-based beverages. In terms of opportunities, the increasing trend of coffee consumption and the strong culture of socializing in coffee shops present significant prospects for business development. Conversely, threats primarily stem from the intense competition among numerous coffee shops in the surrounding area and the shifting preferences of consumers. Based on the SWOT analysis, this study provides insights and recommendations to strengthen Sabri Kupi’s market position, improve promotional efforts, and explore product diversification as strategies to enhance competitiveness in the local coffee industry.